Textbook of Patient Safety and Clinical Risk Management 2020
DOI: 10.1007/978-3-030-59403-9_1
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines and Safety Practices for Improving Patient Safety

Abstract: This chapter explains why clinical practice guidelines are needed to improve patient safety and how further research into safety practices can successfully influence the guideline development process. There is a description of the structured process by which guidelines that aim to increase the likelihood of a higher score are created. Proposals are made relating to (a) the live updating of individual guideline recommendations and (b) tackling challenges related to the improvement of guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 86 publications
0
12
0
1
Order By: Relevance
“…Exposure to potentially infectious biological material is high in the medical profession [ 30 , 31 ], and knowledge of post-exposure procedures minimizes risk [ 32 ]. Recording and monitoring of adverse events such as punctures are standard in healthcare services [ 33 , 34 , 35 ]. The risk evidence of healthcare-associated infections (HAIs) is a motivation for quality and safety improvement [ 36 ]; however, lack of evidence on this in the beautician service sector does not mean that the problem does not exist.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to potentially infectious biological material is high in the medical profession [ 30 , 31 ], and knowledge of post-exposure procedures minimizes risk [ 32 ]. Recording and monitoring of adverse events such as punctures are standard in healthcare services [ 33 , 34 , 35 ]. The risk evidence of healthcare-associated infections (HAIs) is a motivation for quality and safety improvement [ 36 ]; however, lack of evidence on this in the beautician service sector does not mean that the problem does not exist.…”
Section: Resultsmentioning
confidence: 99%
“…Having established protocols, spreading awareness on these, and ensuring their implementation by the staff form the basis for the safe implementation of services. The source of infection can be anyone; the client or the service provider [ 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The current rules for the handling of sharp tools and contaminated instruments in non-medical services, from a logical point of view, should be as restrictive as those used in medical services [ 25 , 26 , 27 , 28 , 29 ]. However, the same views are not held in every country [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…45 Safety problems relating to non-technical skills (NTS) are significant, but appear to be underrepresented in medical and nursing education and training curricula. 47 Typical NTS training topics are described in the literature as performance-shaping factors, planning, preparation and prioritisation, situation awareness and perception of risk, decision-making, communication, teamwork and leadership. 47 NTS elements can be found in the APSQ-3, H-PEPSS, HPPSACS, MSSAPS, PSCNES instruments.…”
Section: Discussionmentioning
confidence: 99%
“…47 Typical NTS training topics are described in the literature as performance-shaping factors, planning, preparation and prioritisation, situation awareness and perception of risk, decision-making, communication, teamwork and leadership. 47 NTS elements can be found in the APSQ-3, H-PEPSS, HPPSACS, MSSAPS, PSCNES instruments. When these NTS are compared with the frameworks and definition of nurse competence, it can be observed that communication and teamwork are typically recurrent elements in the instruments: both dimensions are undeniably crucial to patient safety.…”
Section: Discussionmentioning
confidence: 99%